2021
DOI: 10.3390/ijerph18094710
|View full text |Cite
|
Sign up to set email alerts
|

The Double Mediating Effect of Social Isolation and Emotional Support on Feelings of Entrapment and Motivation for Recovery among Korean Alcoholic Inpatients

Abstract: This study identified the relationship between feeling of entrapment and motivation for change among hospitalized alcoholic patients and examined the double mediating effect model of social isolation and emotional support on this relationship. The study participants were 101 male and female alcoholic patients hospitalized at C hospital, which specializes in alcohol treatment at I city in Korea. PROCESS Macro 3.5 Model 6 was used for analyses of double mediating effects. The results revealed that entrapment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Studies have shown that perceived social support is positively correlated with motivation to recover, and the higher the perceived social support of stroke patients, the stronger their motivation to recover and the more likely they are to contribute to a lower disability rate, which is consistent with the findings of Lee et al (2021) and Darsin Singh et al (2022) . The reason for this is that older patients receive adequate medical coverage through family, friends, health care providers, and society to build confidence in overcoming the disease ( Lobo et al, 2021 ) and are able to follow the rehabilitation advice given by health care providers and follow the plan, which in turn increases the patients’ own motivation to rehabilitate.…”
Section: Discussionsupporting
confidence: 79%
“…Studies have shown that perceived social support is positively correlated with motivation to recover, and the higher the perceived social support of stroke patients, the stronger their motivation to recover and the more likely they are to contribute to a lower disability rate, which is consistent with the findings of Lee et al (2021) and Darsin Singh et al (2022) . The reason for this is that older patients receive adequate medical coverage through family, friends, health care providers, and society to build confidence in overcoming the disease ( Lobo et al, 2021 ) and are able to follow the rehabilitation advice given by health care providers and follow the plan, which in turn increases the patients’ own motivation to rehabilitate.…”
Section: Discussionsupporting
confidence: 79%